Analisis Ekologi Perikanan sebagai Indikator Kerentanan Nelayan Asli Papua Kabupaten Manokwari, Papua Barat - Ferawati Runtuboi; Frida Aprilia Loinenak; Fanny Fransina Simatauw; Yehiel Hendry Dasmasela (Institut Pertanian Bogor, 2015)
The native fishermen are distributed in Manokwari coastal and have currently limited access to fisheries resource. This condition give vulnerable risk to potential utilization of fisheries resources to face vulnerable risk of local fishermen base on ecologycal aspect to take a wisely step to the problem. This research was conducted in April-September in 8 coastal district in Manokwari Regency. The result showed that native fishermen is medium vulnerable with value 0.57 to the number of catches, the composition of the fish and the fishing ground distance area. If this condition continues it will affect the existence of the status of local fishermen wich needs a partisanship in favor of the independence of local fishermen.